Educational Values in ‘Imārah Ya’qūbiyān Novel by ‘Alā’ Al-Aswānī - Endah Kusumawati (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Purpose - This research aims to describe the educational values on ‘Imārah Ya’qūbiyān novel written by ‘Alā’ Al-Aswānī. Design/methodology/approach - The research design is descriptive-qualitative research. The data gained are written words and sentences from the novel that imply an educational value. Findings - The result of the research shows that ‘Imārah Ya’qūbiyān novel contains educational values, i.e.: (1) religious values consisting of (a) human existence before god, (b) human trust in god, and (c) human submission before God; (2) personality values which consist of (a) responsible, (b) honest, (c) hard-working, (d) qanā'ah, and (e) determined; (3) social values which consist of (a) being fair to other human beings, (b) unity of life, and (c) loyalty between humans. Originality/value - Educational values obtained from ‘Imārah Ya’qūbiyān novel is one of the good ways to educate readers in general, and Arabic learners, in particular, to take advantage of Arabic literature. It can be used as educational media in building character to become better individuals in religiosity, personality, social, and can be implemented in real life. Paper type – Research paper